Parameters and solutions of linear and nonlinear oscillators - Rina Ling (International Journal of Mathematics and Mathematical Sciences)
Relationship between existence of solutions for certain classes of nonlinear boundary value problems and the smallest or the largest eigenvalue of the corresponding linear problem is obtained. Behavior of the solutions, as the parameter increases, is also studied.